Entropy statistics and aeronautical evolution - André Bosque Monteiro (2006)
Employing the probabilistic entropy methodology, one of the objectives of this work is to develop a robust and simple tool to be employed in the empirical analysis of airplane configuration and technology evolution. Two specific analyses were performed to validate the procedure. One is the evolution of civil aviation transportation in the jet age (1950-2006) and the other being the evolution of fighter aircraft during the period of 1914 to 2009. An extensive study was carried out in order to select the variables used to describe each aircraft. After the creation of the aircraft databank, the tool developed in the present work takes the variables as input do evaluate two important technological indexes: the convergence and the diffusion. Studies analyzing the combination of the diffusion and the convergence indexes, as well as the critical transition of the airplanes were conducted in this paper. The methodology herein developed can be highly helpful as a decision making tool to be used during the conceptual design phase of an airplane.